Spiritual Needs of Nasopharyngeal Cancer Patients in Yogyakarta - Waliyanti, Ema; Kuswantoro, Febrian (Universitas Muhammadiyah Semarang, 2022)
Background: Spiritual is related to strength or enthusiasm, which aims to get meaning and goals, beliefs, hopes, and beliefs in oneself, others, and including beliefs in God.Objective: To identify the spiritual needs of nasopharyngeal cancer patients in Sleman Regency, YogyakartaMethod: This study uses phenomenological qualitative methods. The informants in this study were 12 informants consisting of 6 patients and six families determined by the purposive sampling method. In-depth interviews did data collection with interview guides. The Open Code 4.02 application assisted data analysis.Result: This study indicates that faith and the purpose of life affect one's self-acceptance of the illness. This condition affects the peace that is felt by the patient, thus affecting the commitment to worship.Conclusion: The spiritual needs of nasopharyngeal cancer patients are suitable, and there are changes in each dimension of spirituality. Meanwhile, we expect the future researchers will conduct research related to the motivation of health workers in the spiritual fulfillment of nasopharyngeal cancer patients